The Optics of the Compound Eye of the Honeybee (Apis mellifera) - Varela, Francisco G. (The Rockefeller University Press, 1970)
The optical system of the compound eye of the worker honeybee, as a representative of the closed-rhabdom type of eye, was investigated and its function analyzed. Measurements of refractive indices of the elements of the optical system were made with an interference microscope. With the use of the resulting measurements, the optical system was analyzed by means of a ray-tracing procedure implemented for the IBM 7094 digital computer, and by means of the Gaussian thick lens formulae. The more detailed results of the ray-tracing technique were used for further analyses. Direct visual confirmation of the focal point was obtained. The rhabdom and the surrounding zone of lower refractive index act together as a wave guide, as demonstrated by the presence of several wave guide modes in the rhabdom. An admittance function was defined as the percentage of the rays reaching the rhabdom with respect to those entering the ommatidium. Good agreement with experimental results was found. The characterization of the visual field of an ommatidium by means of an admittance function permits the analysis of the influence of different stimuli on the eye.